Nutritional Value of Putak: Apparent Metabolisable Energy, and Growth Performance - Catootjie L. Nalle; Marlin R.K. Yowi; Defrys R. Tulle (Hasanuddin University, 2017)
Two experiments were conducted to evaluate nutritional value of putak for broilers. Experiment 1. The apparent metabolisable energy of raw and fermented putak were determined. The experimental design used was completely randomized design with three treatments and four replicates. Total of 64 broilers were randomly distributed to 16 pens. A maize-soybean meal basal diet was formulated and three assay diets were then developed by substituting putak (raw, and fermented, 250 g kg-1, w/w), and maize (500 g kg-1, w/w) of the basal diet. Even though the AME and AMEn values of fermented putak were comparable to that of raw putak and maize, but it was slightly higher than that of raw putak. Experiment 2. Using the AME value of raw putak obtained in Experiment 1, five treatment diets containing 0 to 200 g kg-1 putak were formulated. The body weight gain of broilers fed 150 - 200 g kg-1-1 putak was higher to that of control diet, but it was similar to those fed 50-100 g kg-1 putak. No differences were found in FCR and mortality rate. Feed intake of broilers fed diets containing putak was higher than that of control diet. In conclusion, the AME and AMEn values of putak, fermented putak, and maize were comparable. Putak can be included in broiler diets up to 200 g kg-1 without detrimental effects.